Implementation of Fiqh Tarbawi in the Formation of Students - Abubakar, Alauddin (Al-Fikrah, 2024)
The application of Fiqh Tarbawi in education holds significant potential in shaping students' character through the integration of moral, ethical, and spiritual values. This study employs a qualitative approach with a case study method to explore the challenges and strategies for implementing Fiqh Tarbawi in several educational institutions. Data were collected through in-depth interviews with educators, parents, and students, as well as direct observations in classrooms and school activities. The results indicate that the primary challenges include the lack of understanding among educators regarding the principles of Fiqh Tarbawi, resource limitations, and diverse social dynamics. However, parental involvement, the creation of a positive learning environment, and effective communication between educators and students have proven to enhance the acceptance and understanding of these values. These findings suggest the need for training for educators and the development of a curriculum that is more responsive to social diversity to achieve holistic educational goals.